THE CONTRIBUTION OF ZAKAT ADMINISTRATION AGENCIES TO THE DEVELOPMENT OF ISLAMIC RELIGIOUS EDUCATION (Study: National Zakat Agency of Probolinggo City) - Hidayat, Rudi; Zainullah, Ahmad; Maryam, Siti (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2026)
This study aims to examine the role of the National Zakat Agency (BAZNAS) of Probolinggo City in the development of Islamic Religious Education (PAI) and to identify factors that support the program's success. This study uses a qualitative approach with field research. Data collection was conducted through observation, interviews, and documentation, while data analysis used an interactive model that includes data reduction, data presentation, and conclusion drawing. The results show that BAZNAS of Probolinggo City carries out various efforts to support the development of PAI, such as mapping educational needs, distributing scholarships, religious guidance, providing educational facilities, and strengthening cooperation with various parties. In addition, monitoring and evaluation activities are also carried out periodically to maintain program effectiveness. Supporting factors include the availability of zakat funds, institutional legitimacy, community trust, religious social conditions, human resource capacity, and partnership support. These factors play a role in supporting the program's success, although challenges remain related to funding stability and improving management quality. Thus, zakat management by BAZNAS is not only a temporary assistance, but also leads to community empowerment through the development of Islamic religious education in a sustainable manner.